Zinc contributes to acute cerebral ischemia-induced blood–brain barrier disruption - Zhifeng Qi; Jia Liang; Rong Pan; Wen Dong; Jiangang Shen; Yirong Yang; Yongmei Zhao; Wenjuan Shi; Yumin Luo; Xunming Ji; Ke Jian Liu (Neurobiology of Disease, 2016)
Zinc ions are stored in synaptic vesicles and cerebral ischemia triggers their release from the terminals of neurons. Zinc accumulation in neurons has been shown to play an important role in neuronal death following ischemia. However, almost nothing is known about whether zinc is involved in ischemia-induced blood–brain barrier (BBB) disruption. Herein, we investigated the contribution of zinc to ischemia-induced acute BBB disruption and the possible molecular mechanisms using both cellular and animal models of cerebral ischemia. Zinc greatly increased BBB permeability and exacerbated the loss of tight junction proteins (Occludin and Claudin-5) in the endothelial monolayer under oxygen glucose deprivation conditions. In cerebral ischemic rats, a dramatically elevated level of zinc accumulation in microvessels themselves was observed in isolated microvessels and in situ, showing the direct interaction of zinc on ischemic microvessels. Treatment with a specific zinc chelator N,N,N′,N′-tetrakis(2-pyridylmethyl) ethylenediamine (TPEN), even at 60-min post-ischemia onset, could greatly attenuate BBB permeability in the ischemic rats as measured by Evan's Blue extravasation, edema volume and magnetic resonance imaging. Furthermore, zinc accumulation in microvessels activated the superoxide/matrix metalloproteinase-9/-2 pathway, which leads to the loss of tight junction proteins (Occludin and Claudin-5) and death of endothelial cells in microvessels themselves. Our findings reveal a novel mechanism of cerebral ischemia-induced BBB damage, and implicate zinc as an effective and viable new target for reducing acute BBB damage following ischemic stroke.